The End of Internationalization - Brandenburg, Uwe; De Wit, Hans (International Higher Education, 2011)
Over the last two decades, the concept of the internationalization of higher education has moved from the fringe of institutional interest to the very core. While gaining moral weight, its content seems to have deteriorated. There is an increasing commercialization under the flag of internationalization. This attitude has exacerbated the devaluation of internationalization and the inflation of defensive measures. While in need of more philosophy, we also require a greater sense of reality. We need to rethink and redefine the way we look at the internationalization of higher education in the present time.